La lutte contre la piraterie au large de la Somalie - Vice-amiral Gérard Valin (EchoGéo)
Since 2008, piracy in the Gulf of Aden and off Somalia has considerably increased. France took initiatives and mobilized the international community by escorting vulnerable vessels, by freeing hostages and by working for resolutions at the United Nations. The French means are now used under the European flag, within Atalanta Operation. In parallel, some other operations have been set up by the USA (Task Force 151), NATO and various other States. Piracy goes on but the success rate is getting lower and lower. At the end of the day, only a global approach of the Somalian issues will be able to secure the Gulf of Aden, which is a strategic Sea Line Of Communication for the world trade. Today, only the European Union seems to follow this method.